2009
DOI: 10.1645/ge-1652.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Gyrodactylid (Monogenea) Genus on Gray Bichir, Polypterus senegalus (Polypteridae) from Senegal (West Africa)

Abstract: Diplogyrodactylus martini n. g. et sp., a viviparous monogenean, is described from the gills of gray bichir Polypterus senegalus Cuvier, 1829, in Senegal. This new genus can be readily distinguished from the other described viviparous genera based on the morphology of the attachment apparatus. The haptor is equipped with a pair of centrally positioned hamuli, a simple ventral bar without membrane and 8 pairs of marginal hooks of 2 types, 5 pairs of hooks with well-defined large falculate sickles, and 3 pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Marginal hook shafts long and flexible compared to species of Gyrodactylus. Presence of two muscular pads adjacent to the hamuli, similar to the 'muscular adhesive disks' observed by Přikrylová et al (2009) Table I) Measurements for whole specimens and body parts are presented in Table I. Further, there are 8 pharynx processes and the male copulatory organ (MCO) is positioned off centre to the mid-line of the parasite and posterior to posterior pharyngeal bulb; armed with a principal spine and a single row of 8-10 smaller spines.…”
Section: Monogenea Van Beneden 1858 Gyrodactylidae Cobbold 1864supporting
confidence: 57%
See 2 more Smart Citations
“…Marginal hook shafts long and flexible compared to species of Gyrodactylus. Presence of two muscular pads adjacent to the hamuli, similar to the 'muscular adhesive disks' observed by Přikrylová et al (2009) Table I) Measurements for whole specimens and body parts are presented in Table I. Further, there are 8 pharynx processes and the male copulatory organ (MCO) is positioned off centre to the mid-line of the parasite and posterior to posterior pharyngeal bulb; armed with a principal spine and a single row of 8-10 smaller spines.…”
Section: Monogenea Van Beneden 1858 Gyrodactylidae Cobbold 1864supporting
confidence: 57%
“…The family Gyrodactylidae currently includes 31 genera (Bakke et al 2007, Vianna et al 2007, Přikrylová et al 2009) but of these, sequences are only available for 7 genera. Thus the haplotype of the unknown species was aligned with the following sequences from GenBank: Acanthoplacatus sp.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The author also suggested that the marginal hooklets may prevent the hamuli turning about their longitudinal axis and tearing free of the host skin. In the gyrodactylid monogenean Diplogyrodactylus martini, Přikrylová et al (2009) recorded eight pairs of marginal hooks of two types, five pairs with well-defined large sickles (= blades) and the other three pairs of smaller hooks with well-articulated smaller sickles. The authors suggested that the smaller articulated hooks which are similar to those of Gyrodactylus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-fi ve years later, Mormyrogyrodactylus Luus-Powell, Mashego et Khalil, 2003 was described from Marcusenius macrolepidotus (Peters) (Luus-Powell et al, 2003). Most recently species of the genus Diplogyrodactylus Přikrylová, Matějusová, Musilová, Gelnar et Harris, 2009 were described from P. senegalus and Citharodactylus Přikrylová, Shinn et Paladini, 2017 from Citharinus citharus (Geoffroy Saint-Hilaire) (Přikrylová et al, 2009(Přikrylová et al, , 2017. The most speciose genus of Gyrodactylidae parasitising African fi shes is the cosmopolitan Gyrodactylus von Nordmann, 1832, currently with 36 species described from this continent (Zahradníčková et al, 2016, Přikrylová et al, 2017.…”
Section: Introductionmentioning
confidence: 99%